Restoration of social justice as the basis of criminal policy of the Republic of Belarus - Shidlovsky, Andrey V. (Journal of the Belarusian State University. Law, 2024)
The author of the article examines the phenomenon of social justice and its significance for modern Belarusian society. The approaches and principles of state legal policy in the field of restoring social justice are analysed. The content of social justice in ideological and legal aspects is revealed. Social justice of criminal liability measures is, first of all, considered as a determining condition for the sustainable development of the state and the protection of human rights, and the achievement of social harmony. It is concluded that social justice can be restored with the help of norms that maximally reflect social values in society. The idea of creating a road map for the development of the constitutional and legal foundations of a social state in the format of a single programme document (the concept of «State legal policy for restoring social justice in the Republic of Belarus») is put forward.
Keywords: restoration of social justice; criminal policy; social values; social responsibility; principles; civilisational dimension